PENGARUH KOMPONEN MODAL INTELEKTUAL TERHADAP KINERJA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - Bino Sulaksono (Jurnal Bisnis dan Akuntansi, 2012)
The objective of this research is to investigate and explain the impact of human capital efficiency, structural capital efficiency, and capital employed efficiency on company performance. (ROA, ATO, RG, OCF, ROE, and, EPS). Population in this research is all manufacturing companies listed in Indonesia Stock Exchange during 2008-2010. Samples are obtained through purposives sampling method, in which only 98 of the manufacturing companies listed in Indonesia Stock Exchange meet the sampling criteria and are used as the samples. Multiple regression analysis and hypothesis testing are used as the data analysis method in this research. Based on hypothesis testing, it shows that human capital efficiency positively affects return on assets, revenue growth, and operating cash flow ratio; and do not affect asset turnover, return on equity, and earning per share. Structural capital efficiency positively affects return on assets; negatively affects asset turnover; and do no affect revenue growth, operating cash flow ratio, return on equity, and earning per share. Capital employed efficiency positively affects return on assets, asset turnover, operating cash flow ratio, return on equity, and earning per share; and do not affect revenue growth.